MOTIVASI SISWA MENGIKUTI PENGEMBANGAN DIRI SENI TARI DI SD NEGERI 09 NANGGALO PADANG - Hasnidar Hasnidar; Zora Iriani; Yuliasma Yuliasma (SENDRATASIK UNP, 2013)
Abstract This article aimed to explaining student's motivation infollowing dancing activities as their self-development activities in SD Negeri 09 Surau Gadang Nanggalo Padang. The type of this research was descriptive qualitative research. The data ware collected from observation, interviews, and literature review.  The data were analyzed byusing the phenomenology. The findings indicated that the students weremotivated enoughi following the dancing activiti as their self-development activities. It was seenfromstudents’ enthuseiastic and earnest responseabout theactivities. Most studentsexpressedtheir excitementandwillingness tofollowthe activities.It could be councluded that the students following the dancing activities were those who cared for the dance art itself.